The relationship between certain socio-demographic factors and political cynicism of UPV-CAS students - Dela Cruz, Daysdy
Political cynicism is considered as an essential elements in the political behavior of an individual which affects the working of a political system. That is why there is a need to determine and understand the nature and relationship of the said concept on the different factors which affect the individual. This research attempts to find out whether a relationship exist between certain socio-demographic factors and political cynicism of CAS-UPV students. In the process of answering the said problem, the study also aimed for the following: (1) To find out if there is a relationship between age and political cynicism, (2) To find out if there is a relationship between sex and political cynicism and (3) To find out if there is a relationship between parents' educational attainment and political cynicism. In as much as the researcher wanted to cover all the students of UPV, constraints in time made the researcher to limit the scope of the study to the students of CAS only. Respondents were then proportionally allocated to further ensure that all divisions were properly represented. The data were obtained through the questionnaire and was analyzed both qualitatively and quantitatively with the use of Chi Square and Pearson Correlation. The study revealed that there exist no relationship between the above-mentioned variables and political cynicism. The respondent's feeling of political cynicism is independent of their age, sex, and the educational attainment of their parents. The researcher recommends that further study using other variables must be made in order to further explain the feeling of political cynicism of an individual.It is recommended that other studies of political cynicism must also be conducted indifferent localities so as to determine whether the existence of political cynicism individuals is independent of his or her geographical location. The result of this study might not be the same in other places.